Pengaruh Modal Kerja dan Likuiditas Terhadap Profitabilitas Food and Beverage di Bursa Efek Indonesia - Safitri, Ai Mira; Apriadi, Deri (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of working capital and liquidity on the profitability of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2024. Profitability is measured by Return on Equity (ROE), working capital is calculated from the difference between current assets and current liabilities, while liquidity is measured using the current ratio. This research employs a quantitative approach with descriptive methods and multiple linear regression analysis. The results show that neither working capital nor current ratio has a statistically significant effect on ROE, both partially and simultaneously. The coefficient of determination (R²) of 6.9% indicates that these two variables only explain a small portion of ROE variation. The findings suggest that companies have not yet optimally utilized working capital efficiency and liquidity management to improve profitability. This study contributes to managerial insight by encouraging firms to consider more relevant factors in financial performance strategies. Moreover, the findings support the notion that the influence of the Trade-off and Pecking Order theories in Indonesian corporate finance remains inconsistent.